The biology, diversity and evolution of the broad host-range, promiscuous INCQ plasmids, with an emphasis on the INCQ2 sub-family - Rawlings, Douglas Eric (Stellenbosch : Stellenbosch University, 2015)
Thesis (DSc)--Stellenbosch University, 2014.